Practising Governance: Multi-Party Decision Making in a Multi-Scalar Context - MacCallum, Diana (University of Hertfordshire, 2009)
The much vaunted shift from ‘government’ to ‘governance’ in recent years involves (among other things) increased attention to the participation of ‘stakeholders’ in policy making, a trend affecting not only the actions of politicians but also the day-to-day practice of public servants. In my field, urban/regional planning, this attention has led to a ‘communicative turn’ in the academy; planning practice is increasingly seen as discursive rather than technical. This reframing leads to some significant tensions: between interactive processes and traditional forms of rationalist legitimacy; and between local aspirations and strategic concerns at other geo-political scales. In this paper, I examine how these tensions were negotiated in one case of participatory planning, a meeting of a committee charged with recommending strategies to solve a perceived shortage of industrial land in a remote Australian town. Using discourse-analytical methods derived from systemic functional linguistics, I describe the committee’s construction of a ‘common interest’ between the local and state levels, placing the discursive practices underlying this construction in a context of multi-scalar governance and power relations.